Reciprocal rewards stabilize cooperation in the mycorrhizal symbiosis. - Kiers, E; Duhamel, M; Beesetty, Y; Mensah, J; Franken, O; Verbruggen, E; Fellbaum, C; Kowalchuk, G; Hart, M; Bago, A; Palmer, T; West, SA; et al. (2011)
Plants and their arbuscular mycorrhizal fungal symbionts interact in complex underground networks involving multiple partners. This increases the potential for exploitation and defection by individuals, raising the question of how partners maintain a fair, two-way transfer of resources. We manipulated cooperation in plants and fungal partners to show that plants can detect, discriminate, and reward the best fungal partners with more carbohydrates. In turn, their fungal partners enforce cooperation by increasing nutrient transfer only to those roots providing more carbohydrates. On the basis of these observations we conclude that, unlike many other mutualisms, the symbiont cannot be "enslaved." Rather, the mutualism is evolutionarily stable because control is bidirectional, and partners offering the best rate of exchange are rewarded.